Direct laser writing lithography using a negative-tone electron-beam resist - KIM, H. S.; SON, B. H.; KIM, Y. C.; AHN, Y. H. (Optical Materials Express, 2020)
We used a negative-tone e-beam resist (N-ER) to perform direct laser writing lithography based on a single-photon absorption process with a 405-nm laser source. The linewidth of the N-ER reached 150 nm, which is over three times thinner than that of a conventional photoresist. To optimize the process, the linewidth, lithographic contrast, and aspect ratio of the N-ER were investigated with respect to the dose and baking temperature. We were able to achieve a lithographic contrast of 4.8 and a maximum aspect ratio of 1.43, thereby confirming the superior resolution of the N-ER.We used a negative-tone e-beam resist (N-ER) to perform direct laser writing lithography based on a single-photon absorption process with a 405-nm laser source. The linewidth of the N-ER reached 150 nm, which is over three times thinner than that of a conventional photoresist. To optimize the process, the linewidth, lithographic contrast, and aspect ratio of the N-ER were investigated with respect to the dose and baking temperature. We were able to achieve a lithographic contrast of 4.8 and a maximum aspect ratio of 1.43, thereby confirming the superior resolution of the N-ER.
Keywords: Baking temperature; Direct laser writing; E-beam resist; Electron beam resist; Laser sources; Negative tones; Single-photon absorptions; Superior resolution